2013
DOI: 10.1186/1756-3305-6-193
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations relevant to tsetse control in the Bipindi focus of southern Cameroon

Abstract: BackgroundHuman African Trypanosomiasis (HAT) remains a public health problem in many poor countries. Due to lack of financial resources in these countries, cost-effective strategies are needed for efficient control of this scourge, especially the tsetse vector. It was shown that perennial water sources maintain a favourable biotope for tsetse flies and thus the transmission dynamics of sleeping sickness. The present paper aimed at assessing the transmission dynamics of HAT in a forest environment where the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
15
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
8
15
1
Order By: Relevance
“…The single and mixed infections identified in this study confirm results obtained in tsetse flies and mammals of different African countries [ 16 , 37 – 41 ]. These results show that, whatever the region, single and mixed infections of different trypanosome species are frequent in tsetse flies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The single and mixed infections identified in this study confirm results obtained in tsetse flies and mammals of different African countries [ 16 , 37 – 41 ]. These results show that, whatever the region, single and mixed infections of different trypanosome species are frequent in tsetse flies.…”
Section: Discussionsupporting
confidence: 88%
“…Beside control activities, studies undertaken to improve our epidemiological knowledge on HAT revealed the presence of Trypanosoma brucei gambiense in various domestic and wild animal species of central African HAT foci [ 6 – 10 ]; confirming thus results obtained in West Africa [ 11 – 13 ]. In addition to that, T. b. gambiense was often associated with animal trypanosomes in the same tsetse fly as well as the same animal of central African HAT foci [ 8 , 9 , 14 – 16 ]. In such context where both diseases share the same environment, coexist in the same host and are transmitted by the same tsetse fly species, control measures targeting human and animal diseases can be developed.…”
Section: Introductionmentioning
confidence: 99%
“…It is situated between Lolodorf and Kribi, 75 km from the Atlantic Ocean. Although, a 2004 survey identified four tsetse fly species (GrĂ©baut et al, 2004 ), G. p. palpalis was the only species found in this focus since 2007 (Farikou et al, 2010a , b ; Melachio et al, 2011 ; Tchouomene-Labou et al, 2014 ). Bipindi is surrounded by hills and covers several villages, mainly located along the roads.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on hydrographic network variations, differences in distribution could exist. For example, a forest region's vector distribution could be uniquely different from that of a savannah [31]. In this regard, the identification of distributional patterns is critical for the execution of control measures [3] and for determining the challenge index that reflects tsetse abundance and infection rates in an area [32].…”
Section: Introductionmentioning
confidence: 99%